Effect of seaweed liquid fertilizer of Sargassum wightii on the growth and biochemical characteristics of Abelmoschus esculentus (L.) medikus - C. Anbazhagan, N. Jothinayagi (Recent Research in Science and Technology, 2009)
Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â The effect of different concentrations (20%, 40% 60%, 80% and 100%) of seaweed liquid fertilizer (SLF) of Sargassum wightii on the growth and biochemical characteristics of Abelmoschus esculentus was studied. The low concentration (20%) of S. wightii extract promoted the shoot length, root length, fresh weight, dry weight, chlorophyll, carotenoid, protein, amino acid, reducing sugar, total sugar, Ã‚Â - amylase and -amylase activities in Ã‚Â Abelmoschus esculentus.